Performance of dental students, orthodontic residents, and orthodontists for classification of midpalatal suture maturation stages on cone-beam computed tomography scans - a preliminary study - Sachin Chhatwani; Annahita Arman; Stephan Christian Möhlhenrich; Björn Ludwig; Jochen Jackowski; Gholamreza Danesh (BMC, 2024)
Abstract Background Assessment of midpalatal suture maturation on cone-beam computed tomography (CBCT) scans is performed by visual inspection and is therefore subjective. The extent to which the assessment of midpalatal suture maturation is affected by rater experience has not been adequately explored in the existing literature, thus limiting the availability of evidence-based findings. This study compared the outcomes of classification by dental students, orthodontic residents, and orthodontists. Methods Three different groups of students, orthodontic residents, and orthodontists evaluated 10 randomly chosen CBCT scans regarding midpalatal suture maturation from a pool of 179 patients (98 female and 81 male patients) aged 8 - 40 years which were previously classified by evaluating CBCT scans. The pool was set as benchmark utilizing midpalatal suture maturation classification by one examiner (OsiriX Lite version 11.0; Pixmeo SARL, Bernex, Switzerland). For assessment of intra-rater reliability of the examiners of each group the randomly chosen subjects were reclassified for midpalatal suture maturation after a wash-out period of two weeks by using the same software. Statistical analysis was performed to evaluate intra- and interrater reliability of the three groups with differing experience level. Results Groupwise intra-rater reliability assessment between the classification and reclassification was weak for examiners with a low level of experience (k = 0.59). Orthodontists had highest degree of agreement with regard to benchmark classification with an inter-rater reliability to be considered as moderate (k = 0.68). Conclusions Assessment of midpalatal suture maturation on CBCT scans appears to be a subjective process and is considerably related to the experience level of the examiner. A high level of clinical experience seems to be favorable but does not necessarily ensure accurate results.